EFFECTS OF MANAGEMENT INFORMATION SYSTEMS ON OPERATIONS DECISION MAKING PERFORMANCE AND BUSINESS OPERATIONS PERFORMANCE: MODERATING ROLE OF BUSINESS PROCESS AUTOMATION - Mohanad Mohammed Sufyan Ghaleb; Wael Sh. Basri (Operational Research in Engineering Sciences: Theory and Applications, 2024)
The research aimed to test the effect of management information systems on operational performance with mediating effect of decision-making performance and process automation as a moderating variable in the context of Saudi Arabia. For this purpose, data was collected from the 299 employees of Saudi Arabian textile companies using a convenient sampling technique. Used cross-sectional research design, quantitative research approach, and Partial Least Square (PLS)-Structural Equation Modeling (SEM).  The results show that management information system capabilities have a positive and significant impact on business operation performance. Indirect mediating effect results also show the partial mediation of operations decision making performance among all management information system capabilities and business operations performance. On the other hand, process automation has also shown a significant moderating effect on the relationship of management information system capabilities and business operations performance. The study with significant mediating and moderating effect contributed a novel research finding in the extant literature. The study could also help the regulators focus on the process automation system that could increase the information system of the organization which could support operational performance.